2017
DOI: 10.1080/17483107.2017.1392619
|View full text |Cite
|
Sign up to set email alerts
|

A critical review of hearing-aid single-microphone noise-reduction studies in adults and children

Abstract: This evidence supports the use of SMNR for adults and school-aged children when the aim is to improve listening comfort or reduce listening effort. Future research should test SMNR with infants and children who are younger than 5 years of age. Further development, testing, and clinical trials should be carried out on algorithms not yet available in wearable hearing aids. Testing higher cognitive level for speech processing and learning of novel sounds or words could show benefits of advanced signal processing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 52 publications
0
11
1
Order By: Relevance
“…The modifications to SNR in the current study depended on the HA device and type of processing, with WDRC showing the greatest effect on SNR. The differences between previous results (e.g., Hagerman & Olofsson, 2004; Souza et al, 2006; Naylor & Johannesson, 2009; Chong & Jenstad, 2010; Wu & Stangl, 2013; Alexander & Masterson, 2015; and Brons et al, 2015) and the current results are likely due to differences in test parameters, such as input SNR and type of background noise. The input SNR varied based on individual needs (i.e., SRTn), which could have concealed more systematic effects had multiple fixed SNRs been tested across the psychometric function.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…The modifications to SNR in the current study depended on the HA device and type of processing, with WDRC showing the greatest effect on SNR. The differences between previous results (e.g., Hagerman & Olofsson, 2004; Souza et al, 2006; Naylor & Johannesson, 2009; Chong & Jenstad, 2010; Wu & Stangl, 2013; Alexander & Masterson, 2015; and Brons et al, 2015) and the current results are likely due to differences in test parameters, such as input SNR and type of background noise. The input SNR varied based on individual needs (i.e., SRTn), which could have concealed more systematic effects had multiple fixed SNRs been tested across the psychometric function.…”
Section: Discussioncontrasting
confidence: 88%
“…Several studies have used the phase-inversion approach proposed by Hagerman and Olofsson to quantify acoustic changes to speech and noise post-HA processing, including estimation of the SNR of the HA’s output (Hagerman & Olofsson, 2004; Olsen et al, 2005; Souza et al, 2006; Naylor & Johannesson, 2009; Chong & Jenstad, 2010; Gustafson et al, 2014; Alexander & Masterson, 2015). Using the phase-inversion technique, researchers have demonstrated that WDRC can result in either increases or decreases of the long-term output SNR, depending on both the input SNR and the HA compression settings (Olsen et al, 2005; Souza et al, 2006; Naylor & Johannesson, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The challenges of hearing in noise are particularly problematic for individuals with hearing loss or deafness and those using hearing aids or cochlea implants, who receive limited benefits from noise-reduction techniques (Brons, Houben et al 2012, Chong andJenstad 2018). Approaches to reduce noise often attempt to characterize and subtract background sounds from incoming signals, essentially mimicking the effects of adaptation observed in neural responses to ongoing sounds.…”
Section: Relevance For Hearing Lossmentioning
confidence: 99%
“…Various studies with test subjects or technical measurements for the evaluation of a NRSE can be found in literature [7] which show that a NRSE mostly does not increase speech intelligibility (e.g., [8][9][10][11][12]) but can reduce listening effort. To determine the impact on listening effort, various approaches have been reported, e.g., measuring pupil dilation [13,14], electroencephalography (EEG) [15,16], electrodermal activity [17], response time [18,19], using a dual task paradigm [20][21][22][23][24], or asking for subjective ratings, e.g., using the acceptable noise level (ANL) [25,26], questionnaires [27], or adaptive scaling procedures [28].…”
Section: Introductionmentioning
confidence: 99%